Sealing material for coverage treatment of coal gangue mountains and construction method - CHEN WEI; CHEN XIAO; YANG TENGFEI (2018)
The invention discloses a sealing material for coverage treatment of coal gangue mountains and a construction method. The sealing material is prepared from solid wastes, an additive and water, whereinthe additive is prepared from an ion curing agent and an exciting agent; the ion curing agent accounts for 0.25 percent to 0.5 percent of the mass of solid wastes, the exciting agent accounts for 0.5percent to 0.75 percent of the mass of the solid wastes and the water accounts for 27.5 percent to 29.3 percent of the mass of the solid wastes; the solid wastes are prepared from the following components in percentage by mass: 50 percent to 60 percent of red mud, 22.5 percent to 35 percent of fly ash, 2.5 to 7.5 percent of desulfurized gypsum and 5 percent to 10 percent of lime; the exciting agent is prepared from 30 percent to 35 percent of polymerized active aluminum, 10 percent to 20 percent of sodium hydroxide, 10 percent to 20 percent of sodium silicate and 35 percent to 40 percent of cement; the ion curing agen